What factors influence the choice of first healthcare provider for childhood fever or cough in Ghana? - Immurana, Mustapha; U., Arabi (International Journal of Medicine, 2016)
Malaria and Pneumonia are major killers of children underfive. However, fever and cough are major signs of Malaria and Pneumonia respectively and hence making proper management of fever and cough indispensable in the fight against underfive mortality. This study therefore investigated the factors that influence the choice of first healthcare provider for children with fever or cough in Ghana. The study used the 2014 Ghana Demographic and Health Survey (GDHS) as the main source of data. By employing the multinomial probit model, the study found that urban children, children with higher birth rank, older children, children from the Ga/Dangme, Akan, Mole-Dagbani, Ewe, Mande and Gurma ethnicity and children of mothers with big problems with regards to permission and distance to seek self-medical care were more likely to be given self-medication or to be sent to a traditional practitioner initially for fever or cough. Contrary, mothers with health insurance, aging mothers and wealthy households were less likely to first resort to self-medication or a traditional practitioner in order to seek care for children with fever or cough. The study therefore concludes that ethnicity, residence, permission and distance to seek medical care by mother, mother’s health insurance, household wealth, child’s age, mother’s age and birth order are the factors that influence the choice of first healthcare provider for children with fever or cough in Ghana.